Emotional Reactivity and Proactive Action in Community Heritage Practices in Lithuania - Kelpšienė, Ingrida (Information & Media, 2025)
This article explores the activities and role of heritage communities in Lithuania in shaping collective identity and laying the foundations for civil society. The study is based on two case studies related to cultural heritage preservation practices, each illustrating different types of community mobilization: emotional reactivity to perceived threat, expressed through resistance to the planned logging of the culturally significant Šilavotas Forest, and proactive engagement demonstrated by the community-led initiative to revitalize the abandoned Pumpėnai windmill. Empirical data were collected from the communities’ Facebook pages and analyzed by using content and sentiment analysis, complemented by interviews with community leaders. The analysis reveals how heritage becomes not only a physical entity but also a symbolic resource that strengthens community cohesion and supports civic participation. The examined cases show how heritage preservation efforts are closely linked to community members’ values, worldviews, and emotional attachments to particular sites, expressed through public communication on social media, heritage valuation practices, and cultural memory. The study provides insights into how emotional reactivity and proactive action interact within communities, how collective experiences are given meaning, and how these processes encourage community activities and grassroots civic engagement grounded in the principles of participatory heritage. Moreover, it enhances understanding of the role which heritage communities play in shaping resilient, inclusive, and culturally robust societies in Lithuania.